Changes in the mental health status of the general Chinese population during the COVID-19 pandemic: A longitudinal study - Jin, Kun; Huang, Jing; Teng, Ziwei; Liu, Fangtai; Li, Sujuan; Qiu, Yan; Wu, Haishan; Chen, Jindong; Xiang, Hui; Yang, Min; Xu, Xuelei; Tang, Hui; et al. (Frontiers in Psychiatry, 2022)
The study is based on a longitudinal evaluation of the public, during the initial COVID-19 outbreak in China and eight months after. It aimed to explore the changes in the mental health of the public at the beginning of the pandemic and during the regular epidemic prevention and control. An online survey questionnaire was used to collect data during the initial COVID-19 outbreak (February 10, 2020 –February 18, 2020; T1) and eight months after the outbreak (October 21, 2020 –December 29, 2020; T2). Psychological distress was assessed using the Patient Health Questionnaire-9 (PHQ-9), Self-rating Anxiety Scale (SAS), and Post-traumatic Stress Disorder Checklist (PCL-5). A chi-square test was used to compare the changes in the depression and anxiety scores at T1 and T2, and the correlation between symptoms was analyzed through Spearman’s rank correlation. In T1, 1,200 people were recruited, while 168 people responded in T2. Depression (48.2% to 31.0%; p=0.001) and anxiety (17.9% to 9.5%; p=0.026) symptoms decreased over time; two participants developed post-traumatic stress disorder (PTSD) in T2. The scores of the PHQ-9 scale and the SAS scale were both positively correlated with the score of the PCL-5 scale and negatively correlated with sleep time. During the COVID-19 pandemic, part of the general population’s anxiety and depression significantly reduced with time, and they rarely developed PTSD. PTSD occurrence was related to severe depression and anxiety.